Determination of the solid phase concentration in the course of material solidification - Aktan, O.Yu. (Functional Materials, 2009)
The solidification kinetics is considered. A method has been proposed to determine the solid phase concentration in the course of material solidification by measuring the shear modulus. As an example, the solid phase variation during the solidification of an aqueous gelatine solution has been determined which is used as the matrix of nanosystems are optical chemical sensors has been determined. Досліджено кінетику процесу твердіння. Запропоновано метод визначення концентрації твердої фази у процесі твердіння шляхом вимірювання модуля зсуву. Як приклад, вказаним способом визначено зміну концентрації твердої фази при твердінні водного розчину желатину, який використовується як матриця наносистем - оптичних хімічних сенсорів. Исследуется кинетика процесса затвердевания. Предложен метод определения концентрации твёрдой фазы в процессе затвердевания путем измерения модуля сдвига. В качестве примера указанным способом определено изменение концентрации твёрдой фазы при затвердевании водного раствора желатина, который используется в качестве матрицы наносистем - оптических химических сенсоров.